Bone formation and degradation behavior of nanocrystalline hydroxyapatite with or without collagen-type 1 in osteoporotic bone defects – an experimental study in osteoporotic goats. (June 2016) - Alt, Volker; Cheung, Wing Hoi; Chow, Simon K.H.; Thormann, Ulrich; Cheung, Edmond N.M.; Lips, Katrin S.; Schnettler, Reinhard; Leung, Kwok-Sui
Abstract: The intention of the current work is to assess new bone formation and degradation behavior of nanocrystalline hydroxyapatite with (HA/col-1) or without collagen-type I (HA) in osteoporotic metaphyseal bone defects in goats. After ovariectomy and special low-calcium diet for three months, 3 drill hole defects in the vertebrae of L3, L4, L5, 4 drill hole defects in the right and left iliac crest and 1 drill hole defect at the distal femur were created in three Chinese mountain goats with a total of 24 defects. The defects were either filled with one of the biomaterials or left empty (empty defect control group). After 42 days, the animals were euthanized and the samples were assessed for new bone formation using high-resolution peripheral quantitative computed tomography (HR-pQCT) and histomorphometry with 2 regions of interest. Detail histology, enzymehistochemistry and immunohistochemistry as well as connexin-43 in situ hybridization and transmission electron microscopy were carried out for evaluation of degradation behavior of the materials and cellular responses of the surrounding tissue in respect to the implants. HR-pQCT showed the highest BV/TV ratio ( p = 0.008) and smallest trabecular spacing ( p = 0.005) for HA compared to the other groups in the region of interest at the interface with 1 mm distance to the initially created defect. The HA/col-1 yielded the highest connectivity density (Conn.D) ( p = 0.034) and the highest number of trabeculae (Tb.N) ( p = 0.002) compared to the HA and the control group. Histomorphometric analysis for the core region of the initially created defect revealed a statistically higher new bone formation in the HA ( p = 0.001) and HA/col-1 group ( p = 0.001) compared to the empty defect group including all defect sites. This result was confirmed for site specific analysis with significant higher new bone formation for the HA group for vertebral defects compared to the empty defect group ( p = 0.029). For the interface region, no statistically significant differences were found between the three groups ( p = 0.08). Histology revealed a good biocompatibility without inflammatory reaction for the HA- and HA/col-1 implants with a higher fragmentation of the HA-implant compared to the HA/col-1 biomaterial and formation of new bone in the region between the biomaterial fragments by osteoblasts. Fragmentation was shown by transmission electron microscopy to be caused by multinuclear osteoclast-like cells with degradation of the implant via intracellular incorporation of degraded implant material particles. In conclusion, both nanoparticulate HA with and without collagen type-1 showed better new bone formation compared to untreated drill hole defects in metaphyseal regions of this osteoporotic Chinese mountain goat model with good biocompatibility.